Strong Convergence and Speed up of Nested Stochastic Simulation Algorithm (Communications in Computational Physics, 2020)
In this paper, we revisit the Nested Stochastic Simulation Algorithm (NSSA)for stochastic chemical reacting networks by first proving its strong convergence. Wethen study a speed up of the algorithm by using the explicit Tau-Leaping method asthe Inner solver to approximate invariant measures of fast processes, for which strongerror estimates can also be obtained. Numerical experiments are presented to demonstratethe validity of our analysis.